TRANSFORMASI SOSIAL DI PEDESAAN: STUDI FENOMENOLOGIS PROSES PENDIDIKAN DAN PEMBERDAYAAN MASYARAKAT - Rahmad Santosa (Jurnal Kependidikan, 2011)
The study is aimed at describing the social transformation among members of the village community. The study is qualitative research using phenomenological paradigms for data analyses. The subject consists of poor farmers and pottery makers in the village of Panjangrejo, Bantul Regency. Findings show that the change from being a traditional village of pottery production to a modern village of pottery production begins with innovation by individual pottery makers, is followed by internal dynamics in the community, and finally triggers the birth of the community empowerment and social transformation processes